Analisis Efisiensi dan Efektivitas Pengelolaan APBDes di Desa Yosonegoro, Kecamatan Limboto Barat, Kabupaten Gorontalo - Mulastri Suleman; Zubaidah Rahman; Wahyudin Hasan (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to evaluate the efficiency and effectiveness of the management of the Village Revenue and Expenditure Budget (APBDesa) in Yosonegoro Village, Limboto Barat District, Gorontalo Regency, for the 2019–2023 fiscal years. The research is grounded in the strategic importance of optimal village fund management as a key instrument to promote sustainable rural development. A mixed-methods approach was employed using a case study design, combining quantitative analysis of budget realization data with qualitative insights from interviews with village officials. The findings reveal that expenditure efficiency remains relatively low, with an average efficiency ratio of 94.57%, primarily due to underutilized funds in key sectors such as MSMEs, community empowerment, and cultural programs. In contrast, revenue management performed well, with an average effectiveness ratio of 97.50%, indicating the village's ability to meet most of its revenue targets. These results suggest the need for more thorough program evaluations, increased community participation, and enhanced transparency in financial governance to strengthen fiscal accountability and ensure village development aligns with the actual needs of local residents